2021
DOI: 10.1186/s12916-021-02095-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensive lactation among women with recent gestational diabetes significantly alters the early postpartum circulating lipid profile: the SWIFT study

Abstract: Background Women with a history of gestational diabetes mellitus (GDM) have a 7-fold higher risk of developing type 2 diabetes (T2D). It is estimated that 20-50% of women with GDM history will progress to T2D within 10 years after delivery. Intensive lactation could be negatively associated with this risk, but the mechanisms behind a protective effect remain unknown. Methods In this study, we utilized a prospective GDM cohort of 1010 women without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 78 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…This value is comparable with the daily oral dose of DEA in adult humans (1 mg/kg or 0.1 g dose of DEA for an individual weighing 100 kg) in a three-week clinical study whereby significant health benefits of lowering insulin resistance have been achieved without adverse side effects [17]. Incidentally, the lactation has been reported to correlate with a decrease in the incidence of Type 2 diabetes and circulating lipids in women [56,57].…”
Section: The Levels Of Aza and Dea In Human Body And In The Foodmentioning
confidence: 63%
“…This value is comparable with the daily oral dose of DEA in adult humans (1 mg/kg or 0.1 g dose of DEA for an individual weighing 100 kg) in a three-week clinical study whereby significant health benefits of lowering insulin resistance have been achieved without adverse side effects [17]. Incidentally, the lactation has been reported to correlate with a decrease in the incidence of Type 2 diabetes and circulating lipids in women [56,57].…”
Section: The Levels Of Aza and Dea In Human Body And In The Foodmentioning
confidence: 63%
“…The metabolomics analyses were carried out as described previously ( 12 , 13 ). A total of 500 islets were isolated and collected from the pregnant or non-pregnant group in each trimester.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted metabolomics is a quantitative assay platformed to assess specific metabolites associated with known biochemical pathways or disease processes. Metabolomic profiling has been instrumental in developing metabolic databases and identifying potential disease biomarkers or metabolic pathways associated with diseases like GDM and T2D associated with a GDM history ( 10 13 ). Our previous studies have demonstrated the onset of future T2D after GDM pregnancy was associated with upregulation of glycolipid metabolism involving triacylglycerol and diacylglycerol biosynthesis; but decreased sphingolipid/phospholipid metabolism ( 11 , 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lactation has persistent favorable effects on the cardiometabolic health of women. Recent metabolomic analysis has discovered that lactation decreases circulating glycerolipids (triglycerides and diacylglycerol species) and increases phospholipids and sphingolipids, possibly as a result of suppressing endogenous lipogenesis and upregulating catabolism of lipids to produce breastmilk [ 78 ].…”
Section: Maternal Complications Of Gdmmentioning
confidence: 99%